The Open Library System — Re-invented, Implemented and Working - Hansen, Jens Hofman; Sørensen, Arne (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
A highly modularised and open system is described in this paper, and its ability to support the library’s strategy. By focusing on a single problem, it is possible to solve it in a qualitatively or quantitatively different way that is dictated by business vision and user needs. This results in a highly innovative library system when seen as a whole.